Digital Conglomerates and Their Political Behavior: A Study on the Affiliation of MNC Group Owner Hary Tanoesoedibjo Towards the Presidential Candidacy of Ganjar Pranowo in the 2024 General Election - Aulia Rahmadante Priyanto; Abdul Ghofur (Dinasti Research, 2024)
This article explores the political behavior of digital conglomerates, focusing on Hary Tanoesoedibjo or usually called Hary Tanoe affiliation with Ganjar Pranowo's presidential candidacy in Indonesia's 2024 General Election. Digital conglomerates, such as MNC Group, wield significant influence in shaping public opinion through their diverse media platforms. Hary Tanoe's transition from media facilitator to political actor underscores the intersection of business and politics, raising concerns about media independence and democratic principles. Surveillance indicators are employed to monitor. This research uses a descriptive qualitative method because the researcher wants to examine the political behavior of Hary Tanoe's affiliation with Ganjar. It seeks to analyze the role of digital conglomerates in contemporary politics and understand measures to prevent controversies and violations during the campaign. The results of this research underscore the significant intertwining of business and politics, particularly evident in the case of Hary Tanoe's support for Ganjar Pranowo's presidential bid. This alignment highlights the complex relationship between digital conglomerates, media ownership, and political behavior, shaping electoral dynamics and media coverage. The findings emphasize the importance of transparency, ethical conduct, and adherence to democratic principles in navigating the intricate intersection of business interests and political involvement within Indonesia's digital conglomerates.